Protein and amino acid digestibility: definitions and conventional oro-ileal determination in humans - Hodgkinson, Suzanne M. (Frontiers in Nutrition, 2024)
When assessing protein quality, a correction needs to be made to take into consideration the availability of the amino acids. This correction is based on the digestibility of the amino acids. It is recommended to use ileal (end of small intestine) digestibility as opposed to faecal digestibility. A correction needs to be made for endogenous (gut sourced as opposed to diet sourced) amino acids to give true digestibility as opposed to apparent digestibility. Also, this correction should be made by correcting the amino acid composition for individual amino acid digestibilities as opposed to correcting all amino acids for nitrogen digestibility. Determination of true ileal amino acid digestibility requires the collection of ileal digesta. In the human there are two methods that can be used; naso-ileal intubation and using the ileostomy model. Both are discussed in detail and it is concluded that both are appropriate methods to collect ileal digesta.